2010
DOI: 10.1001/archoto.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adjuvant Radiotherapy on Survival in T1-2N1 Squamous Cell Carcinoma of the Oral Cavity

Abstract: In cases involving T1-2N1 OCSCC in the Surveillance, Epidemiology, and End Results database, the use of RT is associated with statistically significant improved overall survival and cause-specific survival in patients with T2 disease, most strongly in the oral tongue and the floor of the mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 23 publications
5
62
0
1
Order By: Relevance
“…The use of PORT for limited nodal disease is more controversial. Some studies [12,13,[15][16][17] have suggested that the presence of one positive cervical lymph node is 2000 4000 Time (days) 6000 Figure 2. The disease-free survival rate (a) and regional control rate (b) in the cases that were positive for extracapsular spread (ECS); solid lines indicate patients who underwent a surgical treatment at our university hospital and dashed lines indicate patients operated at other institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PORT for limited nodal disease is more controversial. Some studies [12,13,[15][16][17] have suggested that the presence of one positive cervical lymph node is 2000 4000 Time (days) 6000 Figure 2. The disease-free survival rate (a) and regional control rate (b) in the cases that were positive for extracapsular spread (ECS); solid lines indicate patients who underwent a surgical treatment at our university hospital and dashed lines indicate patients operated at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…There are controversial reports about the benefits of PORT [11][12][13][14]. While some reports suggest that PORT for the neck region improves regional control, other reports suggest the opposite, especially in Nl cases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In 8795 patients meeting the inclusion criteria, 54.9% of 3-year overall survival and 43.2% of 5-year overall survival for adjuvant therapy could be gotten compared with 44.4% and 33.4% for surgery alone. More recently, a new analysis with large series (Shrime, 2010) reported that postoperative radiotherapy improved 5-year overall survival rate in patients with T 1-2 N 1 oral squamous carcinoma (41.4% for surgery alone vs. 54.2% for surgery plus radiotherapy). Although statistically significant, slight improvement in survival has to indicate the limitation of single radiotherapy addition, which appeals the need of chemotherapy in the management of advanced HNSCC.…”
Section: Traditional Adjuvant Therapies Improve Outcome Of Advanced Hmentioning
confidence: 99%
“…A combined modality of either surgery with postoperative radiotherapy or chemoradiotherapy is well documented in the treatment of advanced head and neck cancer and a single modality of either surgery or radiotherapy is usually recommended in the early-stage of the disease [3,4]. Transoral surgical resection is the preferred treatment in T1-2 OTC but the management of clinically N0 neck remains controversial between elective ipsilateral selective neck dissection and observation [3,4]. In N1 disease, comprehensive neck dissection is indicated and post-operative adjuvant therapy is not required if pathological staging remains N1 without extracapsular extension [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Transoral surgical resection is the preferred treatment in T1-2 OTC but the management of clinically N0 neck remains controversial between elective ipsilateral selective neck dissection and observation [3,4]. In N1 disease, comprehensive neck dissection is indicated and post-operative adjuvant therapy is not required if pathological staging remains N1 without extracapsular extension [4][5][6]. There are reports of low overall and disease-specific survival rate compared with an early stage of other subsites of oral cavity cancer and also late-stage oropharyngeal cancer [1,2].…”
Section: Introductionmentioning
confidence: 99%